Biopattern: a biomimetic design framework for generating bio-inspired design (biomimicry) - Foo, Chin Thoong (2020)
Some of the best inventions are inspired by nature because nature had been adapting to environmental changes as an algorithm improving itself to solve engineering problems in the most efficient ways. However, there is a huge knowledge gap between engineering and biology where engineers are unable to crossover. The objective of this research is to develop a biomimetic design framework, BioPattern, which bridges this knowledge gap. BioPattern constitutes of TRIZ, SAPPhIRE, and pattern language. It has a pattern-based ontology and a sustainability evaluation, known as Ideal Chart. The method to assess BioPattern is by case study where two different groups of students (controlled group and experimental group) are asked to generate inventive ideas where the experimental group employed BioPattern as the ideation tool. BioPattern is then applied in two industrial problems; centrifugal blower and plastic extruder, conceptually. BioPattern is found to be better in generating ideas with higher novelty. 71% of the ideas generated by the controlled group are of no novelty, 11% low novelty, 7% medium novelty, 11% high novelty, and no new invention. While there are only 8% of the ideas generated the controlled group are of no novelty, 33.5% low novelty, 33.5% medium novelty, 25% high novelty, and no new invention. BioPattern is also able to generate strategies that are practical as the experimental groups are able to fabricate functional machines that are suggested by BioPattern. As for industrial applications, BioPattern suggested the strategy of composite layer to reduce the weight of the impeller of the centrifugal blower, while the strategy of insulation with ceramic for extruder insulation. It can be concluded that BioPattern is able to bridge the biology-engineering gap and it is holistic model which will ease ideation by providing sustainable inspiration from nature.